La Canada et le monde en développement: l'aide et le commerce dans le cadre de la nouvelle politique étrangère canadienne - Rudner, Martin (Études internationales, 1996)
In February 1995, Canada 's Liberal Government issued its first Statement on foreign policy entitled Canada in the World. This Statement viewed international assistance as but one component of an over-arching foreign policy framework geared to the Government's three primary objectives: the promotion of prosperity and employment, the protection of security within a stable global framework, and the projection internationally of Canadian values and culture. This paper argues that among the salient considerations shaping the Government's response to the global economic outlook was the emergence of significant "new players" as partners and competitors of Canada's in international trade and investment, including newly industrializing economies like South Korea, Mexico and Taiwan, and middle income high growth developing countries of Asia and Latin America.